Türkiye’s Contribution to Modernization of Africa’s Security and Defense Autonomy - Özuygun, Mert Efe (Journal of Central and Eastern European African Studies, 2025)
Türkiye's engagement with Africa reflects a strategic evolution from cultural and trade partnerships to transformative security cooperation. This study investigates Türkiye’s contributions to African defense autonomy through defense technology exports, capacity-building programs, and strategic collaborations. Employing case studies of Somalia, Libya, Sudan, and Niger, the article analyzes the impact of these initiatives on regional stability and global power competition. Key findings emphasize Türkiye’s role as a partner distinct from traditional powers, advancing defense technologies, training local forces, and fostering development. The study positions Türkiye as a model for sustainable, equitable, and innovative security engagement in Africa.